Diversity, Interaction and Bioprospecting of Plant-Associated Microbiomes (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Numerous studies have demonstrated that the plant microbiome is highly relevant for the growth and fitness of plants. Plants in ecosystems and agroecosystems can recruit a wide variety of microorganisms, including beneficial microbes which are being studied and applied as biostimulators to improve nutrition and tolerance of plants and as biocontrol of phytopathogens. In this context, this Book contains a selection of articles describing diverse ecological and biotechnological aspects of microbiomes in native and agronomic plants (e.g., pepper, potato, rice and lettuce) created by researchers from Italy, China, Korea, Egypt, Oman, Germany, the USA, and Chile.